The body in the web - Page, Katherine Hall (Page, Katherine Hall. Faith Fairchild mystery, 2023)
Aleford, Massachusetts. The Fairchild family is in lockdown mode as the pandemic spreads. Tom continues his sermons from Zoom; their children, Ben, who's in college, and Amy, a high school senior, are doing remote learning at home. Town halls remain lively and well-attended, despite residents joining from their living rooms. In the midst of one Zoom meeting, damaging images suddenly flash upon everyone's screens. Claudia, the local art teacher, is immediately recognized as the woman who has been targeted. When Claudia is later discovered dead, Faith must journey deep into the dark web to unravel the threads of the woman's history. -- adapted from jacket